New Europe [videorecording (DVD)] - Palin, Michael (BBC Video ; Distributed by Warner Home Video, 2008)
Travel into territory that was once forbidden - the new Europe previously shrouded behind the Iron Curtain. Now that the Iron Curtain has lifted and the Cold War is over, Michael can enjoy a new freedom to roam unhindered across an unexplored swathe of this continent. From Estonia in the north to Turkey in the south, where Europe reaches out to Asia across the Bosphorus, Michael's journey takes him through twenty countries, some Central European, some Eastern European, some straddling continents, and all compelling.